Measuring chronic liver disease mortality using an expanded cause of death definition and medical records in Connecticut, 2004. Issue 9 (18th November 2014) - Ly, Kathleen N.; Speers, Suzanne; Klevens, R. Monina; Barry, Vaughn; Vogt, Tara M.
<x xml:space="preserve">Abstract</x> Aim Chronic liver disease (CLD) is a leading cause of death and is defined based on a specific set of underlying cause‐of‐death codes on death certificates. This conventional approach to measuring CLD mortality underestimates the true mortality burden because it does not consider certain CLD conditions like viral hepatitis and hepatocellular carcinoma. We measured how much the conventional CLD mortality case definition will underestimate CLD mortality and described the distribution of CLD etiologies in Connecticut. Methods We used 2004 Connecticut death certificates to estimate CLD mortality two ways. One way used the conventional definition and the other used an expanded definition that included more conditions suggestive of CLD. We compared the number of deaths identified using this expanded definition with the number identified using the conventional definition. Medical records were reviewed to confirm CLD deaths. Results Connecticut had 29 314 registered deaths in 2004. Of these, 282 (1.0%) were CLD deaths identified by the conventional CLD definition while 616 (2.1%) were CLD deaths defined by the expanded definition. Medical record review confirmed that most deaths identified by the expanded definition were CLD‐related (550/616); this suggested a 15.8 deaths/100 000 population mortality rate. Among deaths for which hepatitis B, hepatitis C and alcoholic liver disease were identified during medical record review, only 8.6%, 45.4% and 36.5%, respectively, had that specific cause‐of‐death code cited on the death certificate. Conclusion An expanded CLD mortality case definition that incorporates multiple causes of death and additional CLD‐related conditions will better estimate CLD mortality.